Y is for yesterday [compact disc, unabridged] - Grafton, Sue (Grafton, Sue. Kinsey Millhone mysteries., 2017)
Kinsey Millhone monitors the release from prison of a sociopath who is determined to exact revenge on a fellow perpetrator who went missing after they sexually assaulted a fourteen-year-old classmate.